Left ventricular outflow tract gradient is associated with reduced capillary density in hypertrophic cardiomyopathy irrespective of genotype. (9th November 2015) - Güçlü, Ahmet; Happé, Chris; Eren, Seyma; Korkmaz, Ibrahim H.; Niessen, Hans W. M.; Klein, Patrick; van Slegtenhorst, Marjon; Schinkel, Arend F.; Michels, Michelle; van Rossum, Albert C.; Germans, Tjeerd; van der Velden, Jolanda
Abstract: Background: Coronary microvascular dysfunction (CMD) is an important feature of hypertrophic cardiomyopathy (HCM), which contributes negatively to symptoms and long‐term outcome. Previous in vivo imaging studies in HCM suggest that left ventricular outflow tract (LVOT) gradient and genetic status are important contributors to CMD. CMD may be caused by reduced capillary density. Here, we investigated whether a reduction in capillary density is related to genetic status or LVOT gradient severity in an in vitro study of HCM cardiac samples. Methods: Using immunofluorescence microscopy, we analysed capillaries (Cap) and cardiomyocytes (CM) in myectomy specimens from 18 HCM patients with maximum left ventricular (LV) wall thickness ≥15 mm. All subjects exhibited significant LVOT obstruction, necessitating septal myectomy. In addition, control myocardium from the LV septal wall was collected at autopsy of 6 individuals that suffered a noncardiac death. Results: CM area was higher in patients with HCM compared to controls. Capillary density was significantly lower in patients with HCM compared with controls (1425 ± 262 vs. 2543 ± 509 Cap/mm 2, P < 0·001), as was the number of Cap per CM corrected for CM area (2·2 ± 0·5 vs. 4·2 ± 0·9 Cap/CM area, P < 0·001). Capillary density did not differ between genotype‐negative and genotype‐positive HCM patients at similar resting LVOT gradients. A significant correlation was present between resting LVOT gradient and CM area ( r = 0·73, P < 0·001), capillary density ( r = −0·74, P < 0·001) and the number of Cap per CM corrected for CM area ( r = −0·82, P < 0·001). Conclusions: Our data indicate that LVOT gradient, rather than genetic status, is associated with reduced capillary density in HCM.